THE EFFECT OF ORGANIZATIONAL JUSTICE ON EXTRINSIC MOTIVATION, INTRINSIC MOTIVATION, JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN THE BANKING SECTOR - Sabara, Saldiansyah; Nasrul, Nasrul; Yusuf, Hayat; Masri, Muhammad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study employs a quantitative explanatory approach to examine the direct effects of organizational justice on extrinsic motivation, intrinsic motivation, job satisfaction, and employee performance in the banking sector. Data were collected using a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that organizational justice has a positive and significant effect on extrinsic motivation, intrinsic motivation, and job satisfaction. Furthermore, extrinsic motivation and intrinsic motivation have a positive and significant effect on job satisfaction, while job satisfaction significantly influences employee performance. These findings emphasize the importance of organizational justice in fostering motivation, enhancing job satisfaction, and improving employee performance within banking organizations